2013
DOI: 10.1152/ajpheart.00837.2012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tachycardia and sympathetic stimulation by cold pressor test on cardiac diastology and arterial function in elderly females

Abstract: Abnormal vascular-ventricular coupling has been suggested to contribute to heart failure with preserved ejection fraction in elderly females. Failure to increase stroke volume (SV) during exercise occurs in parallel with dynamic changes in arterial physiology leading to increased afterload. Such adverse vascular reactivity during stress may reflect either sympathoexcitation or be due to tachycardia. We hypothesized that afterload elevation induces SV failure by transiently attenuating left ventricular relaxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…In subsequent studies, the focus was primarily on changes in LV function during cold pressor testing. Notably, the E/A ratio was significantly decreased but as untwisting velocity increased, diastolic relaxation may not actually be impaired 25,26 . While several studies found only minor changes in EDV, ESV, and EF without achieving statistical significance, cardiac output (CO) and cardiac work index were both significantly increased compared to baseline levels after cold pressor testing.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In subsequent studies, the focus was primarily on changes in LV function during cold pressor testing. Notably, the E/A ratio was significantly decreased but as untwisting velocity increased, diastolic relaxation may not actually be impaired 25,26 . While several studies found only minor changes in EDV, ESV, and EF without achieving statistical significance, cardiac output (CO) and cardiac work index were both significantly increased compared to baseline levels after cold pressor testing.…”
Section: Discussionmentioning
confidence: 96%
“…Notably, the E/A ratio was significantly decreased but as untwisting velocity increased, diastolic relaxation may not actually be impaired. 25,26 While several studies found only minor changes in EDV, ESV, and EF without achieving statistical significance, cardiac output (CO) and cardiac work index were both significantly increased compared to baseline levels after cold pressor testing. This increase can be interpreted as a compensatory adaptation to maintain oxygen supply for cardiac muscle cells.…”
Section: Cardiovascular Responses After Cold Exposurementioning
confidence: 99%
“…Studies on the effects of increased HR on TPR are limited in the literature. Previous studies have observed that pacing reduced TPR [20, 26], while several studies observed no change [18, 27]. Generally, TPR will decrease if pacing has adequately increased the MAP/DBP ratio or CO, as this stimulates the activation of the arterial baroreceptors with subsequent deactivation of sympathetic activity [28].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a previous study reported intensification in speaking rate which was indicated by a decrease in the length of phonation in males and females subjects during the cold pressor test [ 22 ]. Considering that the cold pressor test is an autonomic test that increases the sympathetic nervous system activity [ 23 ], the authors [ 22 ] suggested that increased sympathetic activity induces phonation length. These data do not support the negative association between parasympathetic indices of HRV and the domain 2 of the vocal handicap index.…”
Section: Discussionmentioning
confidence: 99%